El Título de Especialista Universitario en Virtualización del Patrimonio de la Universidad de Alicante. Propuesta formativa. - Jaime Molina Vidal; Francisco Javier Esclapés Jover; Daniel Tejerina Antón; Laia Fabregat Bolufer (Virtual Archaeology Review, 2013)
The University of Alicante has organized the first edition of a specialist degree in Cultural Heritage Virtualization during the academic year 2011-2012. In this paper we intend to show the basis for this project and the program itself. Finally, and from the experience of the first edition, we explain the strategic plan we have defined for the development of future editions, as well as changes that have been introduced, especially in the learning method (offering the option to follow the course online) and the international expansion strategy.